Metastatic Breast Neuroendocrine Cancer in Pregnancy: A Case of an Oncologic Emergency and a Review of Literature. Issue 4 (9th October 2020) - De Luca, Caterina; Tosto, Valentina; Badr, Dominique A.; De Luca, Laura; Porreca, Roberta; Di Renzo, Gian Carlo
Abstract : Abstract: Breast neuroendocrine carcinoma is a rare entity. It constitutes less than 0.5% of breast malignancies, and is usually diagnosed in older women. The occurrence of this type in young patients during pregnancy is extremely rare. Only 2 cases were previously reported. Both were diagnosed at earlier stage with the appearance of a palpable breast mass. Hereby, we present the case of a young patient at 28 weeks' gestation admitted for severe diffuse back pain and neurologic deficit due to spinal cord compression at the level of C5 vertebra, and nerve root compression at the level of L5 vertebrae. To the best of our knowledge, this is the first case of oncologic emergency during pregnancy due to a metastatic poorly differentiated breast carcinoma with neuroendocrine differentiation in the absence of a detectable primary focus of malignancy in the breast. We also discuss the management and the obstetrical outcome of this patient.